2019
DOI: 10.1021/acs.organomet.9b00421
|View full text |Cite
|
Sign up to set email alerts
|

Alkylaluminum Complexes as Precatalysts in Hydroboration of Nitriles and Carbodiimides

Abstract: The metathesis reaction of aluminum(III) dihydride LAlH 2 (1) (L = (ArNCMe) 2 CH, Ar = 2,6-i-Pr 2 C 6 H 4 ) with n-BuLi and n-Bu 2 Mg, respectively, resulted in di-n-butyl aluminum complex LAl(n-Bu) 2 (2). Meanwhile 1 reacted with MeLi producing dimethyl aluminum LAlMe 2 (3). Complexes 2 and 3 were characterized by NMR and elemental analysis, and 2 was additionally studied by single-crystal X-ray diffraction. The reported synthesis allows for access of dialkylaluminum complexes from aluminum-(III) dihydride co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 51 publications
4
62
0
Order By: Relevance
“…Finally, efficient transition-metal-free dihydroboration of nitriles has been achieved with main group element catalysts based on Li, [40] Davit Hayrapetyan was born and raised in Armenia. Mg, [41,42] B, [43] Al [44][45][46][47][48] and Zn [49] systems. All these reports are discussed below with an emphasis on advantages and limitations of hydroboration methods, experimental conditions, substrate scope and functional group tolerance.…”
Section: Transition Metal Catalysts 21 Early Attempts: Mo-catalyzedmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, efficient transition-metal-free dihydroboration of nitriles has been achieved with main group element catalysts based on Li, [40] Davit Hayrapetyan was born and raised in Armenia. Mg, [41,42] B, [43] Al [44][45][46][47][48] and Zn [49] systems. All these reports are discussed below with an emphasis on advantages and limitations of hydroboration methods, experimental conditions, substrate scope and functional group tolerance.…”
Section: Transition Metal Catalysts 21 Early Attempts: Mo-catalyzedmentioning
confidence: 99%
“…[56,57] The majority of main group metal systems developed for hydroboration of nitriles concern aluminum catalysts. [44][45][46][47][48] Thus, the first example of such transformations was reported in 2018 by Cowley and Thomas et al, who employed LiAlH 4 as a precatalyst for a series of hydroborations of alkenes, alkynes and ketones with HBPin. Within the scope of these catalytic trials, the authors also reported hydroboration of 4-trifluoromethylbenzonitrile proceeded with full conversion within 6 h at room temperature using 1 mol% of LiAlH 4 .…”
Section: Main Group Metal Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbonyl hydroboration catalysts include alkaline earth metals,, transition metals, group 13 metal catalysts, lanthanide, actinides, and other unique and sophisticated systems . In addition to the hydroboration of C=O bonds, the selective monohydroboration of carbodiimides to produce amidinates is also of great interest, since these systems play an important role in coordination chemistry …”
Section: Introductionmentioning
confidence: 99%